Central aponeurosis tears of the rectus femoris: practical sonographic prognosis. Issue 11 (27th January 2009) - Balius, R; Maestro, A; Pedret, C; Estruch, A; Mota, J; Rodríguez, L; García, P; Mauri, E
Abstract : Objective: This study is a statistical analysis to establish whether a correlation exists between the level and degree of rectus femoris (RF) central tendon injury and the amount of time that an athlete is unable to participate subsequently, referred to as "sports participation absence" (SPA). Design: Causal–comparative study. Patients: 35 players from two high-level Spanish soccer teams with an injury to the central tendon of the RF based on clinical and ultrasound criteria. Main Outcome Measure: Ultrasound examination was performed with an 8–2 MHz linear multifrequency transducer. All studies included both longitudinal and transverse RF sections. Results: At the proximal level the SPA time is 45.1 days when the injury length is 4.0 cm. This value increases by 5.3 days with each 1 cm increase in the length of injury. In the case of distal level injury, SPA time is 32.9 days when the injury length is 3.9 cm. This value increases by 3.4 days with each 1 cm increase. In the total representative sample, SPA time when the injury length is 4.2 cm corresponds to 39.1 days. This value increases by 4.2 days per length unit. Conclusions: RF central tendon injury at the proximal level is associated with a greater SPA time than at the distal level. Patients with a grade II injury have an SPA time longer than those with a grade I injury whether the injury is located proximal or distal.